2022
DOI: 10.3390/biology11071014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Co-Evolution of Cancer Cells and Cancer-Associated Fibroblasts: Role in Right- and Left-Sided Colon Cancer Progression and Its Clinical Relevance

Abstract: Cancer is a result of a dynamic evolutionary process. It is composed of cancer cells and the tumour microenvironment (TME). One of the major cellular constituents of TME, cancer-associated fibroblasts (CAFs) are known to interact with cancer cells and promote colorectal carcinogenesis. The accumulation of these activated fibroblasts is linked to poor diagnosis in colorectal cancer (CRC) patients and recurrence of the disease. However, the interplay between cancer cells and CAFs is yet to be described, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…For several cancer types including hepatocellular carcinoma, pancreatic cancer, breast cancer, lung cancer, melanoma, and colon cancer it has been demonstrated that tumor cells interaction with CAFs promotes EMT and the metastatic phenotype (Kubo et al, 2016;Domen et al, 2021;Shelton et al, 2021;Ahmad Zawawi and Musa, 2022;Ando et al, 2022;Hu et al, 2022). Direct and indirect mechanisms have been shown to influence tumor metastasis by CAFs: i) ECM remodeling by secretion of collagens, fibronectin, and proteoglycans (Scott et al, 2019); ii) paracrine communication through exosomes, growth factors and cytokines that promote stemness and metastasis, such as: transforming growth factor β -TGFβ, Chemokine (CC motif) ligand 2 (CCL2), Interleukin-6 (IL-6), Hepatocyte growth factor (HGF), Osteopontin (OPN) and Stromal cell-derived factor 1 (SDF-1) (Linares et al, 2020); iii) direct contact with cancer cells and facilitated invasion and select gene transcription (Yamaguchi and Sakai, 2015;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For several cancer types including hepatocellular carcinoma, pancreatic cancer, breast cancer, lung cancer, melanoma, and colon cancer it has been demonstrated that tumor cells interaction with CAFs promotes EMT and the metastatic phenotype (Kubo et al, 2016;Domen et al, 2021;Shelton et al, 2021;Ahmad Zawawi and Musa, 2022;Ando et al, 2022;Hu et al, 2022). Direct and indirect mechanisms have been shown to influence tumor metastasis by CAFs: i) ECM remodeling by secretion of collagens, fibronectin, and proteoglycans (Scott et al, 2019); ii) paracrine communication through exosomes, growth factors and cytokines that promote stemness and metastasis, such as: transforming growth factor β -TGFβ, Chemokine (CC motif) ligand 2 (CCL2), Interleukin-6 (IL-6), Hepatocyte growth factor (HGF), Osteopontin (OPN) and Stromal cell-derived factor 1 (SDF-1) (Linares et al, 2020); iii) direct contact with cancer cells and facilitated invasion and select gene transcription (Yamaguchi and Sakai, 2015;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with left-sided CRC (LCRC), right-sided CRC (RCRC) is usually associated with poor prognosis, and also presents more advanced N stage, larger tumor size, poorly differentiated tumors, as well as higher probability of lymphatic vascular invasion ( 48 ). In addition, RCRC also presented higher hypermethylation and higher microsatellite instability (MSI) frequency than LRCR ( 26 , 49 ). Higher risk score was associated with worse survival rate and higher MSI-high proportion, which was consistent with phenotypic characteristics of RCRC.…”
Section: Discussionmentioning
confidence: 99%
“…CRC is a highly complex and heterogeneous disease, contributed by cancer epithelial cells and the TME [ 36 ]. TME constitutes multiple cellular components neighbouring to the colonic crypt of cancer epithelial cells including fibroblasts, immune cells, and endothelial cells and intricate network of extracellular matrix (ECM) which have been reported to promote colorectal carcinogenesis and confer chemoresistance [ 37 ].…”
Section: Crcmentioning
confidence: 99%